2009
DOI: 10.1089/ten.tea.2008.0567
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Implantation of Bone Marrow–Derived Mesenchymal Stem Cells with Fibrin Micro Beads to Repair a Critical-Size Bone Defect in Mice

Abstract: Fibrin microbeads (FMBs) made using thermal treatment of fibrin drops in oil can efficiently isolate mesenchymal stem cells (MSCs) from bone marrow (BM) and other similar sources and culture them continuously in suspension culture. The pure mesenchymal profile of MSCs isolated using FMBs and their differentiation potency to different mesenchymal lineages were previously described in detail. In the current study, MSCs were isolated from the BM of (GFP+) C57/bl mice using FMBs. Addition of pro-osteogenic medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 43 publications
0
38
0
Order By: Relevance
“…After 2 months, results showed that defects filled with bone-like tissue had a Ca/P ratio similar to that of the native bone while no repair was seen in the control animals without implants or when the defect was filled with FMBs alone. 102 In addition to efficiently repairing bone, the use of FMBs successfully eliminated stages of culturing the MSCs on tissue culture plastics, trypsinizing the cells that can damage their cellular membrane receptors, performing cell passages, and finally loading the cells onto the scaffolds. 102 Furthermore, FMBs may be used as a matrix onto which cells can be maintained for a long time at room temperature.…”
Section: Different Forms Of Fibrin Applications In Bone Tissue Enginementioning
confidence: 99%
See 1 more Smart Citation
“…After 2 months, results showed that defects filled with bone-like tissue had a Ca/P ratio similar to that of the native bone while no repair was seen in the control animals without implants or when the defect was filled with FMBs alone. 102 In addition to efficiently repairing bone, the use of FMBs successfully eliminated stages of culturing the MSCs on tissue culture plastics, trypsinizing the cells that can damage their cellular membrane receptors, performing cell passages, and finally loading the cells onto the scaffolds. 102 Furthermore, FMBs may be used as a matrix onto which cells can be maintained for a long time at room temperature.…”
Section: Different Forms Of Fibrin Applications In Bone Tissue Enginementioning
confidence: 99%
“…102 In addition to efficiently repairing bone, the use of FMBs successfully eliminated stages of culturing the MSCs on tissue culture plastics, trypsinizing the cells that can damage their cellular membrane receptors, performing cell passages, and finally loading the cells onto the scaffolds. 102 Furthermore, FMBs may be used as a matrix onto which cells can be maintained for a long time at room temperature. The matrix preserves their proliferation and bone differentiation potential, which in turn facilitates cellular transformation between different research and/or clinical centers.…”
Section: Different Forms Of Fibrin Applications In Bone Tissue Enginementioning
confidence: 99%
“…The phenomena would be mainly caused by the alterations of Ca, P, Fe, S, Zn and Mg. The gender difference was significant in the relation between Ca and P. The role of Ca/P has already been shown in bone [29,30], auditory ossicles [31], and teeth [32,33]. Furthermore, the Ca/P ratio plays a role for vascular calcification of aorta and coronary arteries [12,34].…”
Section: Discussionmentioning
confidence: 82%
“…55,56 Moreover, these microspheres can also serve as a construct to support in vitro MSCs expansion and osteogenic differentiation, which consequently formed a calcified matrix embedding osteoblasts, 57 and further to induce ectopic bone formation 58 as well as reconstruction of critical-size bone defects in vivo. 59 However, the rapid degradation rate and poor mechanical stability of fibrin have been stated as the main limitation for bone tissue engineering. 54 To overcome this problem, composite microspheres were developed to stabilize the fibrin matrix.…”
Section: Polymeric Micro-/nanospheresmentioning
confidence: 99%